2013
DOI: 10.1371/journal.pone.0057239
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Methods for Targeted Mutagenesis in Zebrafish Using Zinc-Finger Nucleases: Data from Targeting of Nine Genes Using CompoZr or CoDA ZFNs

Abstract: Recently, it has been shown that targeted mutagenesis using zinc-finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs) can be used to generate knockout zebrafish lines for analysis of their function and/or developing disease models. A number of different methods have been developed for the design and assembly of gene-specific ZFNs and TALENs, making them easily available to most zebrafish researchers. Regardless of the choice of targeting nuclease, the process of generating mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 45 publications
0
59
0
Order By: Relevance
“…Previously, we targeted 26 genes with ZFNs or TALENs and successfully generated multiple knockout alleles for 21 genes (Sood et al 2013). In addition to the substantial reduction in cost and increased ease of design and assembly for CRISPR targets compared to ZFNs and TALENs, our data showed that the CRISPRs were significantly more efficient in generating genetic mutations (Fig.…”
Section: Direct Comparison Of Crispr/cas9 To Zfns and Talensmentioning
confidence: 69%
See 1 more Smart Citation
“…Previously, we targeted 26 genes with ZFNs or TALENs and successfully generated multiple knockout alleles for 21 genes (Sood et al 2013). In addition to the substantial reduction in cost and increased ease of design and assembly for CRISPR targets compared to ZFNs and TALENs, our data showed that the CRISPRs were significantly more efficient in generating genetic mutations (Fig.…”
Section: Direct Comparison Of Crispr/cas9 To Zfns and Talensmentioning
confidence: 69%
“…Injected fish were grown to adulthood and screened for germline transmission of CRISPR-induced mutations by fluorescence PCR (Sood et al 2013). Each putative founder fish was crossed with a wild-type fish and embryos were harvested at 24-72 h post-fertilization in 96-well plates, one embryo per well.…”
Section: Genomic Dna Extractionmentioning
confidence: 99%
“…Injection of mRNA, founder screening, and identification of cbfb heterozygous adult fish has been described in detail previously. 30 For each experiment, cbfb-Del4 and cbfb-Ins4 were genotyped by fluorescent polymerase chain reaction (PCR) using a mixture of M13F-tailed (59-TGTAAAACGACGGCCAGT-39) cbfb-specific forward primer (59-ATGCTCGGGCCTGGCTTTCT-39), 6-FAM-labeled M13F primer, and PIG-tailed (59-GTGTCTT-39) cbfb-specific reverse primer (59-AGG GGCGTGAGTTAGAGT-39) in the PCR mix. 30 Genotyping of fixed samples has been performed as above but using a different PCR mix (Sigma RED Extract-N-Amp PCR Ready Mix R4775 REDExtract-N-Amp PCR Ready Mix, R4775; Sigma-Aldrich).…”
Section: Generation Of Cbfb Mutants and Genotypingmentioning
confidence: 99%
“…32,33 The selected CompoZr ZFN pair targeted a specific region within cbfb exon 3 ( Figure 1A). 30 Among 9 mutations identified 30 from 6 germline-transmitting founders, we selected 2 mutations predicted to cause frameshifts with premature terminations, cbfb hg10 (c.215delACCT, p.N72IfsX25) and cbfb hg11 (c.215insACCT, p.H74PfsX43), denoted here as cbfb del4 and cbfb ins4 ( Figure 1B). In order to test whether the mutations lead to loss of cbfb expression, we evaluated the presence of cbfb transcripts in cbfb del4/del4…”
Section: Generation Of Zebrafish Cbfb 2/2 Mutantsmentioning
confidence: 99%
“…To date, three major types of customizable endonucleases have been developed, namely zinc finger nucleases (ZFNs) [513], transcription activator-like effector nucleases (TALENs) [10,1421] and clustered regularly interspaced short palindromic repeats (CRISPR) RNA-guided Cas9 (CRISPR/Cas) nucleases [2232]. All three classes have been shown to cause efficient target gene disruption in zebrafish [5,6,8,9,14,17,19,27,3339]. Nevertheless, each platform differs in the ease of their construction methods, potential off-target activities and the theoretical targeting range.…”
Section: Introductionmentioning
confidence: 99%